The Formal Opening and Dedication of the Fellowship Hall: Independence United Methodist Church. May 26, 1974 - (:unkn) unknown (Tignall, Georgia: Independence United Methodist Church)
The Formal Opening and Dedication of the Fellowship Hall: Independence United Methodist Church. May 26, 1974. W.L. Buffington, pastor. Event program. Tignall, Georgia. United States.
1 electronic document. independence-methodist_program_19740526.pdf. 12 pages. 85658395 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Independence United Methodist Church (Wilkes County, Ga.); Tignall (Ga.); Anthony, Gus; Bamford, Sophia B.; Bamford, Thomas L.; Barksdale, B.T.; Boyd, J.W.; Boyd, John W.; Brahe, May H.; Buffington, D.S.W.L.; Buffington, W.L.; Buretta, Joe; Buretta, Michael; Buretta, Samantha; C.M., Azmon; Cameron, J.H.; Cannon, William; David, Grace; Driggers, Bruce; Driggers, Connie; Driggers, Jenette; Driggers, Mike; Driggers, Terri; Fawcett, John; Freeman, Alton P.; Freeman, Lamar; Gavis, W.A.; Hall, Billy; Hall, Marie; Hall, Pam; Hall, Pamela Ann; Harrison, Boyd Roy; Harrison, Don; Harrison, Donald; Harrison, Dud; Harrison, Mike; Harrison, Roy; Johnson, Debra; Johnson, William; Kent, Guy; Latimer, L.W.; Lindsey, W.F.; Lloyd, Harvey; Mason, Lowell; Moss, J.A.; Norman, W.F.; Norman, William; O'Pry, Henry; Parker, Theodore; Pierce, George F.; Price, E.W.; Rhodes, Jack M.; Rhodes, Jack; Roberson, A.L.; Roberson, Gwyn; Roberson, Hamp; Roberson, Jerry; Roberson, Larry; Roberson, Lisa; Roberson, Sandy; Sale, Jarvis; Sale, Robert; Smith, Kathryn; Smith, W.R.; Taylor, Helen; Taylor, Robert L.; Taylor, Robert; Toombs, Robert; Truitt, Wanda; Tyler, David; Tyler, Herman L.; Tyler, Herman; Vickery, Fred; Wansley, H.M.; Wesley, Charles; Whitener, Dan; Whitener, David Andrew; Whitener, Milton; Wiggins, Thomas B.; Wiggins, Thomas Boyd; Wilkinson, E.J.; Wilkinson, N.; Wootten, Ellen; Wootten, G.H.; Wootten, J.T.; Wootten, L.A.; Wootten, Samuel; Wootten, Thomas L.; Wootten, W.L.; Wootten, William; Wright, C. B.; Wright, Charles B.; Wright, Rebecca Gore; Zundel, John